Atraḫasīs, behind the First Sin That Cried to Heaven and Related Matters - Winitzer, Abraham (Journal of ancient Near Eastern religions, 2023)
This paper inquires about the source of human blood in the Biblical Primeval History, beginning with the report in the Cain and Abel story of bloodshed and a related cosmic-upsetting noise. It is posited that this unique report and the sophisticated case of ancient philology extending to it from the Eden story and relating ʾādām, “Adam,” dām, “blood,” and ʾădāmâ, “earth” are inspired by the Mesopotamian myth of Atraḫasīs, in which an equally complex case of philological speculation concerning anthropogeny also relates to an outstanding account of bloodshed and a cosmic-upsetting noise. This occasion of a posited transformation of Mesopotamian lore in the Primeval History is considered within the broader context of this intercultural contact and its underlying philological and theological assumptions and motivations.